Fundamental limitations of the decay of generalized energy in controlled (discrete-time) nonlinear systems subject to state and input constraints - Selek, István; Ikonen, Enso (Zielona Góra: Uniwersytet Zielonogórski)
This paper is devoted to the analysis of fundamental limitations regarding closed-loop control performance of discrete-time nonlinear systems subject to hard constraints (which are nonlinear in state and manipulated input variables). The control performance for the problem of interest is quantified by the decline (decay) of the generalized energy of the controlled system.
Keywords: decay rate maximization; Lyapunov function; nonlinear control systems